PRINSIP BAGI HASIL PADA PERBANKAN SYARI’AH (JURNAL HUKUM SEHASEN, 2015)
Islamic banking at present experiencing rapid growth, as evidenced by the presence of a wide range of syari’ah banks and conventional bank runs its business according to syari’ah principles. Syari’ah principle is a principle derived from the values of Islam, which is used as a guide for syari’ah banking operations. Characteristics of Islamic banking is the use of profit-sharing system, which distinguishes it from conventional banking system to interest. This research aims to find out more about the basic principles on Islamic banking, and to analyze more clearly the comparison between the results of the banking system of syari’ah with the conventional banking system of interest. The method used in this study is the research literature, with qualitative research methodology, using the approach to law, historical approach, comparative approaches and conceptual approaches. The results showed that the basic principle on Islamic banking consists of: principles of cooperation, trust principles, precautionary principle, principle of responsibility and fairness. Comparison between the results of the banking system of syari’ah with the conventional banking system in the interest lies in the concept of getting the benefits, in addition to the basic differences between Islamic banking system with the conventional banking lies in the differences in philosophical aspects, operational aspects, social aspects and aspects organization.   Keywords: Principle of  Profit sharing, Islamic Banking.